Enhancing corrosion resistance of AISI 4130 steel through optimized HVOF tungsten carbide coatings - Moghanian, Amirhossein; Mohammadi, Mohammad Abedini; Ansari, Javad; Asadi, Parviz; Akbari, Mostafa; Yazdi, Morteza Saghafi; Safaee, Sirus (Elsevier, 2025)
In the petroleum and petrochemical industries, equipment integrity is jeopardized by aggressive environments promoting corrosion. This study investigates the impact of high-velocity oxygen fuel (HVOF) thermal spray coating parameters on the quality and corrosion resistance of tungsten carbide coatings applied to AISI 4130 steel. Critical parameters such as powder feed rate (60-72 g/min) and spray intensity (6.7-7.2 bar) were optimized for treated samples S3 and S5. Scanning electron microscopy (SEM) images were analyzed to assess coating thickness and quality. Mechanical properties were evaluated using Vickers hardness tests, revealing a substantial increase in hardness from 225 Vickers for the uncoated sample (S0) to 2010 and 2060 Vickers for coated samples S3 and S5, respectively, and in sample S5 compared to S3, the value increased by 2.46% (*p < 0.05). Corrosion resistance was assessed through Tafel and Nyquist tests, indicating that the HVOF coatings exhibited superior corrosion resistance compared to the control sample. Notably, sample S5 demonstrated lower current density and a more positive corrosion potential than S3, suggesting enhanced protective performance against corrosive ions. The Nyquist plot analysis further confirmed that sample S5 exhibited a higher corrosion resistance due to its uniform distribution of tungsten carbide and reduced porosity. Ultimately, the HVOF coating with a spray intensity of 7.2 bar and a powder feed rate of 72 g/min (sample S5) was identified as the optimal configuration for maximizing corrosion resistance.
Keywords: Corrosion resistance; HVOF coating; Tungsten carbide; AISI 4130 steel; Thermal spray techniques